Clean-Room lithographical processes for the fabrication of Graphene biosensors - Cabral, Patrícia D. (2020)
This work is on developing clean-room processes for the fabrication of electrolyte-gate graphene field-effect transistors at the wafer scale for biosensing applications. Our fabrication process overcomes two main issues: removing surface residues after graphene patterning and the dielectric passivation of metallic contacts. A graphene residue-free transfer process is achieved by using a pre-transfer, sacrificial metallic mask that protects the entire wafer except the areas around the channel, source, and drain, onto which the graphene film is transferred and later patterned. After the dissolution of the mask, clean gate electrodes are obtained. The multilayer SiO2/SiNx dielectric passivation takes advantage of the excellent adhesion of SiO2 to graphene and the substrate materials and the superior impermeability of SiNx. It hinders native nucleation centers and breaks the propagation of defects through the layers, protecting from prolonged exposition to all common solvents found in biochemistry work, contrary to commonly used polymeric passivation. Since wet etch does not allow the required level of control over the lithographic process, a reactive ion etching process using a sacrificial metallic stopping layer is developed and used for patterning the passivation layer. The process achieves devices with high reproducibility at the wafer scale.